Quality Teaching and Learning in the Health Sciences - Essack, Sabiha; Naidoo, Indirani; Oosthuizen, Frasia; Bodenstein, Johannes; Brysiewicz, Petra; Suleman, Fatima (South African Journal of Higher Education, 2016)
Quality teaching is a central tenet to the retention and success of students in higher education but teaching quality measures and indicators have not enjoyed sufficient debate and discourse within the higher education sector. The Faculty of Health Sciences at the University of KwaZulu-Natal investigated the use of various programme and module statistics as well as student and peer evaluations of teaching to inform quality improvements in teaching and learning. Quantitative data allowed benchmarking in relation to internal University targets and national norms and pointed to the student cohorts who collectively required teaching and learning interventions but was found to have limited use in improving individual teaching practice. Qualitative data from students and peers was best able to highlight strengths and weaknesses and provided the most useful data to inform changes in teaching practice as it engendered and enhanced reflective practice. The Organization for Economic Co-operation and Development (OECD) report on quality teaching in higher education found that most evaluation instruments were related to teaching input indicators and that there was a dearth of instruments to evaluate the impact of teaching, i.e. there was no explicit evaluation criteria linking teaching input to learning outcome. The challenge for the second cycle of institutional reviews/audits will thus be (1)identifying suitable qualitative indicators/measures for quality teaching , (2) striking the correct balance between quantitative and qualitative teaching quality indicators/measures, and (3), ensuring that such indicators, both quantitative/qualitative address teaching impact/learning outcomes in addition to teaching inputs.